Butterfly Gastric Bypass - Essam Abdel-Galil (Highlights on Medicine and Medical Science Vol. 7, 2021)
Perforation, bleeding and malignancy of the bypassed stomach, duodenum and biliary tree are serious complications and fatal if not early diagnosed, which is an impossible situation in RYGBP and mini bypass. Patients who qualify for bariatric surgery are candidates for butterfly gastroplasty. Body mass index (BMI) should be more than 30 or more than 25 with presence of comorbidities. The success of butterfly gasroplasty as a Laparoscopic restrictive procedure, as more than 1000 cases have done (after 2008) in many centers and Ahmed Maher teaching hospital Cairo Egypt. We recommend laparoscopic butterfly gastric bypass (BB) to be the technique of choice in morbid obesity as it has all the advantages of mini gastric bypass in addition to the gastro-gastric banded outlet allows easily the endoscopic and radiological diagnosis treatment of the bypassed stomach.